2012
DOI: 10.1088/1674-4926/33/7/073003
|View full text |Cite
|
Sign up to set email alerts
|

Structural and optical properties of Zn-doped β-Ga2O3films

Abstract: Intrinsic ˇ-Ga 2 O 3 and Zn-doped ˇ-Ga 2 O 3 films were prepared using RF magnetron sputtering. The effects of the Zn doping and thermal annealing on the structural and optical properties are investigated. In comparison with the intrinsic ˇ-Ga 2 O 3 films, the microstructure, optical transmittance, optical absorption, optical energy gap, and photoluminescence of Zn-doped ˇ-Ga 2 O 3 films change significantly. The post-annealed ˇ-Ga 2 O 3 films are polycrystalline. After Zn doping, the crystallization deteriora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…[10][11][12][13][14][15] While the traditional molecular beam epitaxy (MBE) growth method can produce high quality Ga 2 O 3 materials, the challenge of slow growth rates still need to be addressed. 11,12 Among the limited efforts towards heteroepitaxy of b-Ga 2 O 3 thin films on foreign substrates, [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] none has reported heteroepitaxial Ga 2 O 3 films with good electrical properties.…”
Section: Ultrawide Bandgap (Uwbg) Gallium Oxide (Ga 2 O 3 )mentioning
confidence: 99%
“…[10][11][12][13][14][15] While the traditional molecular beam epitaxy (MBE) growth method can produce high quality Ga 2 O 3 materials, the challenge of slow growth rates still need to be addressed. 11,12 Among the limited efforts towards heteroepitaxy of b-Ga 2 O 3 thin films on foreign substrates, [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] none has reported heteroepitaxial Ga 2 O 3 films with good electrical properties.…”
Section: Ultrawide Bandgap (Uwbg) Gallium Oxide (Ga 2 O 3 )mentioning
confidence: 99%
“…There are some experimental works dedicated to high amount (> 1%) Zn incorporation into Gallium Oxide for different purposes (as summarized in Table I). W. Yue et al studied the effect of Zn doping (2 wt%) by magnetron sputtering showing that with Zn doping the band gap slightly was reduced from 4.90 to 4.87 eV [22]. Similarly, it was found that with the increase of Zn dopant concentration up to ~ 3%, the crystal lattice expands, the energy band gap shrinks, and the oxygen vacancy concentration decreases [23].…”
Section: Intrinsic and Zn-doped P-type Ga2o3 A Reviewmentioning
confidence: 99%
“…Over the last years, numerous of Ga 2 O 3 -based solar blind photodetectors have been demonstrated with different structures including original bulk, thin films, and even nanostructures. , Among these, β-Ga 2 O 3 thin film solar-blind photodetectors have grabbed much research interests in practical applications due to their easy growth, low cost, and better repeatability. As we all know, an ideal efficient solar-blind photodetector should have the following properties including high signal current-to-dark ratio, high sensitivity, high spectral selectivity, high speed, high stability, and low fabrication cost. ,, In addition, ultralow dark current is often required for a high-performance photodetector, which means that the semiconductor materials used should have high resistance. For β-Ga 2 O 3 , due to its n-type feature with self-compensation for oxygen defects, one effective way to obtain high-resistance and high insulating Ga 2 O 3 thin films is to produce high-quality, defect-free β-Ga 2 O 3 single crystal films without oxygen vacancies. ,, Until now, β-Ga 2 O 3 thin film on other substrates has been widely reported by different growth techniques such as thermal evaporation, radio frequency magnetron sputtering, , chemical vapor deposition, pulsed laser deposition, molecular beam epitaxy, , metal–organic chemical vapor deposition, , microwave irradiation approach, atomic layer deposition, , and mechanical exfoliation method . However, limited by the large lattice mismatch, the above traditional heteroepitaxial growth method cannot meet the requirements for preparing CMOS-compatible, high-quality silicon-based β-Ga 2 O 3 thin films at a large scale.…”
Section: Introductionmentioning
confidence: 99%
“…For β-Ga 2 O 3 , due to its n-type feature with selfcompensation for oxygen defects, one effective way to obtain high-resistance and high insulating Ga 2 O 3 thin films is to produce high-quality, defect-free β-Ga 2 O 3 single crystal films without oxygen vacancies. 21,41,42 Until now, β-Ga 2 O 3 thin film on other substrates has been widely reported by different growth techniques such as thermal evaporation, 43 radio frequency magnetron sputtering, 44,45 chemical vapor deposition, 46 pulsed laser deposition, 47 molecular beam epitaxy, 48,49 metal−organic chemical vapor deposition, 50,51 microwave irradiation approach, 52 atomic layer deposition, 53,54 and mechanical exfoliation method. 55 However, limited by the large lattice mismatch, the above traditional heteroepitaxial growth method cannot meet the requirements for preparing CMOS-compatible, high-quality silicon-based β-Ga 2 O 3 thin films at a large scale.…”
Section: Introductionmentioning
confidence: 99%